2018
DOI: 10.1111/bjh.15456
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of bone marrow endothelial progenitor cells in acute graft‐versus‐host disease patients after allotransplant

Abstract: Graft-versus-host disease (GVHD) is a major complication after allogeneic haematopoietic stem cell transplantation (allo-HSCT) that is frequently associated with bone marrow (BM) suppression, and clinical management is challenging. BM endothelial progenitor cells (EPCs) play crucial roles in the regulation of haematopoiesis and thrombopoiesis. However, little is known regarding the functional roles of BM EPCs in acute GVHD (aGVHD) patients. In the current prospective case-control study, reduced and dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 67 publications
2
31
0
Order By: Relevance
“…The vascular endothelial cells (ECs) are particularly vulnerable to toxic effect of preparative regimen drugs, such as Busulfan, cyclophosphamide, and fludarabine which are widely used prior to hematopoietic stem cell transplantation (HSCT) [ 1 ]. Several studies have indicated that bone marrow (BM) vascular niche was impaired after HSCT [ 2 5 ], which was associated with poor Graft Function [ 3 , 4 ]. The healthy ECs, their expressed cytokines, and signal molecules in BM microenvironment play an important role in normal hematopoiesis and repopulation [ 6 8 ], while the function of the impaired ECs, the changes of expressed cytokines and signal molecules, and how do these changes affect hematopoietic cell function are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The vascular endothelial cells (ECs) are particularly vulnerable to toxic effect of preparative regimen drugs, such as Busulfan, cyclophosphamide, and fludarabine which are widely used prior to hematopoietic stem cell transplantation (HSCT) [ 1 ]. Several studies have indicated that bone marrow (BM) vascular niche was impaired after HSCT [ 2 5 ], which was associated with poor Graft Function [ 3 , 4 ]. The healthy ECs, their expressed cytokines, and signal molecules in BM microenvironment play an important role in normal hematopoiesis and repopulation [ 6 8 ], while the function of the impaired ECs, the changes of expressed cytokines and signal molecules, and how do these changes affect hematopoietic cell function are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…After allogeneic hematopoietic stem cell transplantation (also HSCT), the number of EPCs decreased with dysfunction in patients with PGF and aGVHD, manifested as decreased migration and angiogenesis, and increased reactive oxygen levels and apoptosis. The damage degree of EPCs is positively correlated with the level of reactive oxygen species and apoptosis (Kong et al, 2013;Cao et al, 2018).…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…The following multicolour flow cytometry panel were applied to quantify ECs in BM: anti-CD34-PE/Cy7, anti-CD309-PE, and anti-CD133-APC (BD Biosciences, CA, USA). ECs were identified as CD34 + CD309 + CD133 + , and the relative EC frequency was expressed as a fraction of BMMNCs [23][24][25][26][27]. Samples were collected on a BD LSRFortessa flow cytometer and the compensation adjustion as well as data analysis were accomplished via a BD LSRFortessa software.…”
Section: Characterization Of Bm Ecsmentioning
confidence: 99%